Self-revelation and concealment in Caesar’s De bello Gallico: Cicero, Orgetorix, and the Belgae - Altman, William Henry Furness (Classica - Revista Brasileira de Estudos Clássicos, 2015)
Building on the work of others who have seen an allusion to the First Triumvirate in the tripartite Gallic conspiracy led by Orgetorix, this article shows how Caesar reveals himself as formidable between the lines of De bello Gallico, and particularly in its famous opening.